Chemotherapy for Metastatic Gastric Cancer: Does Age Matter? A Single-Center, Retrospective, Real-World Study. (September 2022) - Liao, Po-Wei; Cheng, Shao-Bin; Chou, Cheng-Wei; Lin, Hsin-Chen; Lin, Cheng-Hsien; Chen, Tsung-Chih; Hsu, Chiann-Yi; Jerry Teng, Chieh-Lin; Shih, Yu-Hsuan
Background: Palliative chemotherapy is the preferred standard of care for patients with metastatic gastric cancer (mGC). It remains uncertain whether older patients with mGC would benefit from palliative chemotherapy. This study aimed to investigate the clinical impact of palliative chemotherapy in older patients with mGC. Methods: This single-institute, retrospective, and real-world study included 428 patients with mGC between January 2009 and December 2019. Among them, 306 who received palliative chemotherapy were further stratified into 2 groups according to age: ≤70 (n = 236) and >70 (n = 70) years. The clinical demographics, outcomes, and hematologic toxicities of chemotherapy were compared between the 2 groups. Prognostic factors were determined using the Cox proportional hazards model. Results: Of the screened 428 patients, older patients had worse overall survival (OS) than younger patients. Among patients who received chemotherapy (n = 306), patients aged >70 and ⩽70 years had comparable progression-free survival (PFS) and OS. The incidence of severe hematologic toxicity was similar between the 2 groups. The Eastern Cooperative Oncology Group performance status of 2 or more metastatic sites, elevated carbohydrate antigen 19-9 level, high neutrophil-to-lymphocyte ratio (NLR), and undergoing palliative gastrectomy were independent prognostic factors for OS. Notably, age >70 years was not a significant factor for poor OS. Conclusions: Older age of >70 years might not be considered an obstacle to administering palliative chemotherapy to patients with mGC.